2014
DOI: 10.1016/j.crohns.2014.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Rectal microRNAs are perturbed in pediatric inflammatory bowel disease of the colon

Abstract: Background and Aims Changes in intestinal microRNAs have been reported in adult patients with ulcerative colitis or Crohn’s disease. The goal of this study was to identify changes in microRNA expression associated with colitis in children with inflammatory bowel disease. Methods Rectal mucosal biopsies (n=50) and blood samples (n=47) were collected from patients with known or suspected inflammatory bowel disease undergoing endoscopy. Rectal and serum microRNA levels were profiled using the human nCounter® pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 46 publications
1
49
0
Order By: Relevance
“…Zahm et al identified CD-associated miRNAs in the sera of 6 adolescent children with active disease 32 and IBDassociated miRNAs in the sera of 18 UC and 11 CD pediatric patients. 33 MiR-142-5p, miR-143, miR-595, and miR-24, which were screened for were not identified. Iborra et al 34 compared miRNA expression levels in the sera of groups of 9 adult patients with active and inactive CD (mostly colonic) and UC to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Zahm et al identified CD-associated miRNAs in the sera of 6 adolescent children with active disease 32 and IBDassociated miRNAs in the sera of 18 UC and 11 CD pediatric patients. 33 MiR-142-5p, miR-143, miR-595, and miR-24, which were screened for were not identified. Iborra et al 34 compared miRNA expression levels in the sera of groups of 9 adult patients with active and inactive CD (mostly colonic) and UC to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study involving atherosclerosis-susceptible endothelium, miR-10a expression was found to be downregulated and the expression of its predicted target HOXA1 was significantly upregulated (50). Likewise, miR-24 expression significantly increased in the inflamed colons of pediatric inflammatory bowel disease (IBD) patients, suggesting that the upregulation may be a host response to curtail inflammatory signaling (51). Similarly, IL-10 was reported to suppress production of proinflammatory cytokines such as TNF-␣, IL-6, and IL-12 by selectively inducing the upregulation of miR-187 (48).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, at 60 days p.i., THC was found to selectively upregulate the expression of a group of 19 miRNAs, 6 of which (miR-10a, miR-24, miR-99b, miR-145, miR-149, and miR-187) have been previously identified to target proinflammatory molecules such as cytokines and transcription factors (48)(49)(50)(51)(52)(53)(54). Among these, miR-10a was demonstrated to maintain intestinal homeostasis by targeting the proinflammatory cytokine IL-12/IL-23p40 in dendritic cells (DCs) (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Very recently, a study identified a number of deregulated microRNAs in the rectal tissue of pediatric patients. 10 Our recent studies revealed that miR-124 is epigenetically regulated specifically in pediatric patients with active UC and this leads to increased STAT3 activity in the colonic tissue of these patients. 11 However, further investigation is needed to define the role and function of the microRNA-signature specific to pediatric UC patients.…”
Section: Introductionmentioning
confidence: 97%